Implementasi Instrumen Asesmen Argumentasi Ilmiah Materi Laju Reaksi - Ismiatul Zaroh; Muntholib Muntholib; Ridwan Joharmawan (Orbital: Jurnal Pendidikan Kimia, 2022)
Scientific argumentation is a critical part of scientific practice that should be learned by learner in the science classroom. Scientific argumentation can deepen students' understanding and make their reasoning apparent. Integrating argumentation in instruction necessitates the availability of assessment instruments. This study aims to develop a scientific argumentation test and investigate students' argumentation skills on reaction rates. This study applied a research and development design to develop a scientific argumentation test followed by a survey on students' scientific argumentation skills. The analysis of the validity and reliability of the scientific argumentation test involved three experts and 199 high school students. Meanwhile, the survey on students' scientific argumentation skills involved 86 high school students. The expert panel gave an average score of 94.8% (very worthy) to the developed scientific argumentation test. The empirical analysis of the test shows that all items (9 essay items) were valid with reliability of 0.777. The survey showed that students' abilities in: making claims were moderate (56.59%), providing evidence were very weak (18.35%), and making explanations were also very weak (14.21%). The results of this study imply that learning strategies that can improve students' scientific argumentation skills are needed.